A rare case of abdominal aortic aneurysm quadfurcation - Tri-Thuc Nguyen; Thanh-Phong Le (Annals of Vascular Surgery - Brief Reports and Innovations, 2023)
Bilateral absence of common iliac arteries or aortic quadfurcation is an extremely rare congenital vascular variant in which aorta terminated directly into four branches: two internal iliac arteries and two external iliac arteries. In the case of this anomaly combined with an abdominal aortic aneurysm, the treatment method should be carefully selected regarding various factors, especially the possibility of pelvic perfusion preservation.This article reports a case with an abdominal aortic aneurysm quadfurcation which was successfully treated by open repair using a transperitoneal approach with preservation of two internal iliac arteries.